Differences in Financial Performance of Bank Muamalat Indonesia and Bank Syariah Indonesia in 2020-2023 - Galuh Aprillina Natassa; Karina Ervi Munanda Putri (MJK PUBLISHER, 2026)
This study aims to analyze the differences in financial performance between Bank Muamalat Indonesia (BMI) and Bank Syariah Indonesia (BSI) during the 2020–2023 period using Return on Equity (ROE) and Operating Expenses to Operating Income (BOPO) ratios. A quantitative comparative approach was employed using secondary data obtained from the quarterly financial statements of both banks. Data analysis was conducted using the Independent Sample T-Test to determine whether significant differences existed between the financial performance of the two Islamic banking institutions. The results indicate significant differences in both ROE and BOPO ratios between BMI and BSI. Bank Syariah Indonesia recorded a higher ROE than Bank Muamalat Indonesia, indicating stronger profitability and a greater ability to generate returns from shareholders’ equity. In addition, Bank Syariah Indonesia achieved a lower BOPO ratio, reflecting better operational efficiency and more effective cost management. These findings demonstrate that Bank Syariah Indonesia outperformed Bank Muamalat Indonesia in terms of profitability and operational efficiency during the observation period. This study contributes to the literature on Islamic banking by providing a comparative analysis using quarterly financial statement data and offers useful insights for banking management, investors, and regulators.